A Review of Metaverse's Definitions, Architecture, Applications, Challenges, Issues, Solutions, and Future Trends - Al-Ghaili A.M.; Kasim H.; Al-Hada N.M.; Hassan Z.B.; Othman M.; Tharik J.H.; Kasmani R.M.; Shayea I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Architecture; Augmented reality; Interactive computer graphics; Internet of things; Network architecture; Condition; Future trends; Game; Graphic; Internet of thing; Metaverse privacy; Metaverses; Research areas; Web 3.0; Virtual reality